Change in body size and mortality: a systematic review and meta-analysis. (13th November 2016) - Karahalios, Amalia; English, Dallas R; Simpson, Julie A
Abstract: Background : Observational studies have reported that weight loss in later life is associated with an increased risk of mortality. However, the association with weight gain is unclear. We conducted a systematic review and meta-analysis of prospective studies assessing the association of weight gain and loss, and mortality. Methods : We searched PubMed, Scopus and Web of Science for articles published before 5 September 2015. We included prospective studies that reported enough information to extract hazard ratios (HRs) with the corresponding 95% confidence intervals (CIs) for the association between weight gain and/or weight loss, and all-cause and cause-specific mortality. The estimates were pooled using a random-effects model. Meta-regression models were fitted to explore sources of potential between-study heterogeneity. Results : A total of 25 (providing data from 437 772 participants with 34 038 deaths from all causes) and 24 studies (434 694 participants with 31 978 deaths) presented results for the exposures, weight loss and weight gain. Weight loss compared with a stable weight was associated with an increased risk of all-cause (pooled HR: 1.45; 95% CI: 1.34, 1.58), and cardiovascular disease (CVD) mortality (1.50; 1.32, 1.70) and a slightly increased risk of cancer mortality (1.19; 0.97, 1.46). Weight gain was associated with an increased risk of CVD mortality (1.21; 1.07, 1.36) and a slightly increased risk of all-cause mortality (1.07; 1.01, 1.13) and cancer mortality (1.04; 0.96, 1.13). Considerable heterogeneity was observed; the method used to ascertain body size and the proportion of the baseline sample included in the final analysis explained most of the heterogeneity. Conclusion : Weight loss and weight gain in midlife are associated with increased risk of all-cause and CVD mortality.